2019
DOI: 10.1002/ptr.6305
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin promotes microglial M2 polarization and degradation enzyme expression

Abstract: Two kinds of microglia are known, classical M1 and alternative M2 phenotypes. Amyloid β (Aβ), a critical cause of Alzheimer's disease (AD), promotes M1 microglial polarization, leading to neuroinflammation and neuronal death. M2 microglia play important roles in anti-inflammatory effects, Aβ clearance, and memory recovery in AD. Therefore, increasing of M2 microglia is expected to recover from AD. We previously found that naringenin, a blood-brain barrier penetrating compound, decreased Aβ deposits and recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Nge was used as a positive control, as in our previous report. 7 The levels of IL-1β, TNF-α, and IL-6 were significantly increased, whereas those of IL-10 were decreased compared with the levels in the control group after LPS treatment. IL-1β, TNF-α, and IL-6 productions were significantly inhibited after the 12-hour pretreatment with either 1 and 10 µM HED or Nge (Figure 3(C)-(E)).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Nge was used as a positive control, as in our previous report. 7 The levels of IL-1β, TNF-α, and IL-6 were significantly increased, whereas those of IL-10 were decreased compared with the levels in the control group after LPS treatment. IL-1β, TNF-α, and IL-6 productions were significantly inhibited after the 12-hour pretreatment with either 1 and 10 µM HED or Nge (Figure 3(C)-(E)).…”
Section: Resultsmentioning
confidence: 82%
“…18 Moreover, M1 microglia express specific proteins, including CD16/32 and iNOS, and M2 microglia express Arginase I, CD206, and Ym1. 7 To confirm whether HED affects microglial polarization, 1 and 10 µM HED were used to pretreat primary microglia for 2 hours followed by treatment with 100 ng/mL LPS for another 24 hours (Figure 4(A)). The analysis results showed that CD206 expression was significantly downregulated, while that of iNOS was upregulated after LPS treatment (Figure 4(B) and (C)).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations